2014
DOI: 10.1007/s12199-014-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and adherence of Umezu polyphenols in the Japanese plum (Prunus mume) in a 12-week double-blind randomized placebo-controlled pilot trial to evaluate antihypertensive effects

Abstract: Objectives Medications or lifestyle changes to prevent or improve hypertension often press considerable efforts on patients suffering from mild hypertension. Capsules including Umezu polyphenols (UP), polyphenols in Japanese plums, may help them to control their blood pressure (BP). The aim of this study is to evaluate the effectiveness of UP on BP and its safety. Methods A total of 15 healthy workers without antihypertensive medication who had some concerns about their BP, preferably normal-high BP or hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Since UP is confirmed safe for animals and humans, it should be considered as a good food source that lacks toxicity. 19,20) Acknowledgments This work was supported by research Grants from the Regional Innovation Strategy Support Program (Wakayama Kihokukichu Area) of the Ministry of Education, Culture, Sports, Science and Technology of Japan and also by Heisei 27 and 28 year (FY2015 and FY2016) research Grants from the Kishu-Tanabe Ume Promotion Committee. The authors wish to acknowledge Dr. Ryoichi Araki, Associate Professor of Faculty of Education, Wakayama University, for his help in interpreting the significance of the results of this study.…”
Section: Involvement Of Citric Acid In Antimicrobial Activitymentioning
confidence: 99%
“…Since UP is confirmed safe for animals and humans, it should be considered as a good food source that lacks toxicity. 19,20) Acknowledgments This work was supported by research Grants from the Regional Innovation Strategy Support Program (Wakayama Kihokukichu Area) of the Ministry of Education, Culture, Sports, Science and Technology of Japan and also by Heisei 27 and 28 year (FY2015 and FY2016) research Grants from the Kishu-Tanabe Ume Promotion Committee. The authors wish to acknowledge Dr. Ryoichi Araki, Associate Professor of Faculty of Education, Wakayama University, for his help in interpreting the significance of the results of this study.…”
Section: Involvement Of Citric Acid In Antimicrobial Activitymentioning
confidence: 99%
“…Dietary supplements such as ginkgo biloba, resveratrol, quercetin, curcumin, catechin, and omega-3 fatty acids are known to inhibit platelet activation [ 6 , 7 , 8 , 9 ]. In recent decades, Prunus mume fruit extracts (PMFE) has been reported to have various health benefits [ 10 , 11 , 12 , 13 ], including improvements of blood flow [ 14 ] and inhibition of platelet aggregation [ 15 ]. We have previously reported that PMFE improves cognitive impairment induced by decreased blood flow through an inhibitory effect on the toll-like receptor 4(TLR4)/myeloid differentiation primary response 88/ nuclear factor (NF)-κB signaling pathways [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…"umesu", a by-product obtained during the manufacture of pickled Japanese apricot with high salt concentration) 8 and reported many physiological activities of umesu phenolics, including antibacterial 9 and antihypertensive effects. 10 By performing a quantitative characterization of the phenolics in the Nanko-mume fruit, we found that the fruit contains a significant amount of polyphenols. The flesh of a fully matured fruit contains up to 1% of phenolics on a dry weight basis.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we have purified a phenolic fraction (umesu phenolics) chromatographically using a nonpolar macroporous adsorbent resin from the salt extracts (i.e. “umesu”, a by‐product obtained during the manufacture of pickled Japanese apricot with high salt concentration) and reported many physiological activities of umesu phenolics, including antibacterial and antihypertensive effects . By performing a quantitative characterization of the phenolics in the Nanko‐mume fruit, we found that the fruit contains a significant amount of polyphenols.…”
Section: Introductionmentioning
confidence: 99%